Large arc voltage fluctuations and droplet formation in electric arc wire spraying - Newbery, A; Grant, P (2003)
The diameter of droplets in electric arc wire spraying is critical in determining the microstructure, porosity and oxide content of the resulting sprayed coatings. Droplet diameter controls dynamic and thermal behaviour in the spray, and the splashing and spreading behaviour of droplets at deposition. In electric arc wire spraying, the droplet diameter is determined by a combination of the melting behaviour of the feedstock wires in a direct current arc, combined with primary and secondary atomisation processes under the action of a high velocity atomising gas. The high frequency arc voltage variations during electric arc spraying of Fe-0·8C have been investigated and arc voltage fluctuations related to atomisation events occurring at the wire tips during spraying. A simple analytical model has been proposed which allows the diameter of primary droplets produced by atomisation to be calculated from the wire feedrate and the average time period for material removal, which was obtained from the voltage traces. Primary droplets were then assumed to undergo secondary atomisation according to correlations from the literature, and resulting droplet diameters were compared with diameters measured by experiment. Despite uncertainties in some of the thermophysical data and dynamic conditions during atomisation, predicted droplet diameters were in good agreement with experimental mass mean droplet diameters obtained under a range of atomising gas pressures, arc voltages and wire feedrates.